Synthesis of hydroxymethylfurfural from cellulose using green processes: A promising biochemical and biofuel feedstock. (13th March 2016) - Rout, Prasant Kumar; Nannaware, Ashween Deepak; Prakash, Om; Kalra, Alok; Rajasekharan, Ram
Abstract: Inedible, lignocellulosic biomass has been recognized as most promising renewable resource for the production of high value bio-chemicals. The pretreated biomass or isolated cellulose is a biopolymer of glucose used as a stating material for the synthesis of 5-hydroxymethylfurfural (HMF). HMF is listed among the top 10 bio-based chemicals by USA Department of Energy and it acts as feedstock for deriving a number of commodity products (Bonzell and Petersen, 2010, Green Chem. 12, 539). In present review, we have systematically summarized the catalytic reaction for the synthesis of HMF from pretreated biomass/isolated cellulose using green processes. Further, through catalytic approach, HMF is translated into industrial important chemicals (2, 5-diformylfuran, furan-2, 5-dicarboxylicacid, 2, 5-furandimethanol, furfuraylalcohol, etc) or high calorific value biofuel (2, 5-dimethylfuran, 2, 5-dimethyltetrahydrofuran, 2, 5-bis(alkoxymethyl)furans, etc). In the profitable scale of HMF production, levulinic acid (LA) is generated as a major byproduct. Besides HMF, this review also outlines the catalytic strategy for the conversion of LA to industrially important chemicals along with the biofuel additives. Finally, the bio-toxicity of synthesized chemicals, which connected into different functional groups have been summarized to meet the criteria of the green technology for commercialization. Graphical abstract: Synthesis of cellulose derives industrially important compounds through HMF.